Policies on tuberculosis treatment: A review of healthcare strategies and interventions - fithriany fithriany (Science Midwifery, 2023)
This study aims to conduct a comprehensive analysis of policies related to tuberculosis (TB) treatment, with a focus on examining healthcare strategies and interventions. A systematic literature review was employed as the research methodology to gather relevant scientific evidence from various published sources. The eligibility criteria for study inclusion were based on factors such as study type, population sample, and research quality. The search strategy involved utilizing academic journal search engines from online databases, including PubMed, Web of Science, Scopus, and Springer Link. Relevant keywords such as "policies," "tuberculosis treatment," "healthcare strategies," and "interventions" were used to conduct the search, with a time restriction of the past 10 years to ensure the inclusion of recent studies. The analysis process involved reviewing the titles and abstracts of identified studies, applying the pre-defined PICO (Population, Intervention, Comparison, Outcome) criteria to determine their relevance. Studies that met the inclusion criteria were selected for full-text review and critical appraisal. The critical appraisal assessed the methodological quality and rigor of each study to ensure the reliability of the findings. The results of the literature search and study selection process were presented in a flow diagram, depicting the number of studies identified, excluded, and ultimately included in the analysis. The findings of the systematic literature review will provide insights into the various healthcare strategies and interventions implemented globally to address TB treatment. The analysis will examine the effectiveness of different policies, identify gaps or areas for improvement, and highlight successful approaches in tuberculosis management.